Synthesis and characterization of Moringa oleifera copper nanoparticles shows toxic effect on fish Cirrhinus mrigala - Dr. Chikkappa Udagani; Dr. Shivaraj Yallappa; Suman D P; Shruthinag N (International Journal of Pharma and Bio Sciences, 2020)
Fish is an healthy food for humans and nutritious diet due to the presence of high protein levels, beneficial fat and various sources of vitamins and minerals. Though the fish is a healthy food, a concern about the toxic effect of copper nanoparticles on fish was reported. The objective of the present work is to study the effect of Moringa oleifera CuNPs on fish Cirrhinus mrigala fish species. Moringa oleifera is a fast growing and drought resistant tree which contains rich amount of nutrients and vitamins -.The initial concentration of the CuNPs colloidal solution was 350 nm by TEM Transverse Electron Microscope micrograph and UV-visible spectrum and X-Ray diffraction. The freshwater fish, Cirrhinus mrigala was exposed to lethal concentration of copper nanoparticles synthesized via chemical reduction method using C for a period of 4 days exposure, where the value of LC50 of CuNPs was obtained 2ppm. For the static renewal of exposure, the lethal concentration of copper nanoparticles were 0.5, 1, 1.5 and 2ppm including control group. Some Changes in fish behaviour, like changes in Erratic swimming, restlessness, surfacing and hyper activity etc, were observed at the time of exposure periods. This work seems to be useful in analysing not only the disadvantages of using CuNPs but also problems related to their use.